ԼՂՀ հարկային քաղաքականությունը ներդրումային միջավայրում - Ղահրամանյան, Հ. Շ.
This article is about the fixed from the view point o f tax policy rules and the creation of duspicious conditions fo r the invsetments in NKR. The author o f the article also suggests the waysand directions o f creating that conditions for native andr foreign investors. В данной работе изложены правила, установленные законом с точки зрения налоговой политики, как для местных, так и для иностранных инвесторов. В статье также предложены направления по созданию благоприятного инвестиционного климата.
Keywords: Տնտեսագիտություն; Արցախ